The Application of the CIPP Evaluation Model in Educational Programs in Indonesia - Alanshori, M. Zainuddin; Maulidi, Ahmad; Kusaeri, Kusaeri; Suparto, Suparto; Muhlisin, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to systematically review and analyze the trends in the use of the CIPP (Context, Input, Process, Product) evaluation model across various educational programs, as well as its strengths, weaknesses, and recommendations for implementation. The research employed a systematic literature review method, consisting of four stages: identification, selection, eligibility assessment, and inclusion. Article searches were conducted through Google Scholar, ScienceDirect, and SpringerLink using the keyword “CIPP model of education evaluation,” resulting in 833 articles. Most of these articles were published in international journals and conference proceedings from various countries. After applying the inclusion criteria, 26 articles were selected that specifically discussed the application of the CIPP model in education. The findings indicate that the CIPP model is widely used as a comprehensive and flexible evaluation framework, especially in Asia, between 2019 and 2025. It is effective in assessing program context, resource input, implementation processes, and outcomes. However, challenges include the complexity of mixed-method data analysis and the need for skilled evaluators. This review recommends modularizing evaluation instruments, providing standardized training for evaluators, integrating digital technology, adapting local indicators, and developing flexible policy support. These strategies aim to enhance the relevance, efficiency, and impact of the CIPP model in education evaluation practices.